Loss analysis of oil-free twin-screw expanders for recovering energy in fuel cell systems by means of p-θ diagrams. (15th June 2020) - Wang, Chuang; Xing, Ziwen; Sun, Shizhong; He, Zhilong
Abstract: Twin-screw expanders extend their application and become more and more favored in fuel cells. For twin-screw expanders in fuel cells, pressure loss is a key factor to affect their performance, and thus is investigated by means of the indicator diagram in this paper. Hence, a series of pressure transducers were arranged in consecutive positions of the casing to measure the pressure variation inside working chamber of three expanders with different suction port area and rotor length. By analyzing the measured p-θ diagrams, the features of working process are identified. Moreover, the relevant influence mechanisms of rotating speed and suction back pressure on losses including suction loss and mechanical loss are discussed. Results show that the suction throttling pressure loss and leakage shows a significant influence on the expander performance. The suction port area is suggested to be larger than the maximum value of filling area, and it had better to set both radial and axial filling port in order to decrease the pre-expansion pressure loss. Finally, a method to judge the operating state of expanders according to the measured p-θ diagrams is proposed. Results indicate that the rotor length of 60 mm may be just suitable for the developed expanders. Highlights: Indicator diagrams of three expanders for fuel cell application is measured. The features of working process are identified. Suction loss and mechanical loss are accurately quantized. A method to judge operating state of expanders based on p-θ diagrams is proposed.